Privacy-Preserving Record Linkage: An international collaboration between Canada, Australia and Wales - Conrad Pow; Karey Iron; James Boyd; Adrian Brown; Simon Thompson; Nelson Chong; Charlotte Ma (International Journal of Population Data Science, 2017)
ABSTRACT